Multiplex B Cell Characterization in Blood, Lymph Nodes, and Tumors from Patients with Malignancies - Zirakzadeh, A Ali; Marits, Per; Sherif, Amir; Winqvist, Ola (The Journal of immunology (1950), 2013)
B lymphocytes contribute to immune surveillance, by tumor-specific Abs and Ag presentation to T lymphocytes, but are insufficiently studied in humans. In this article, we report a flow cytometric investigation of B lymphocyte subpopulations in blood, lymph nodes (LNs), and malignant tissues from 20 patients operated on because of advanced solid tumors. The CD19+ compartment in peripheral blood was essentially unaltered in patients, as compared with healthy control subjects. In metastatic LNs, signs of B lymphocyte activation were observed, as evidenced by increased proportions of plasmablasts and CD86-expressing cells. In tumor-infiltrating B lymphocytes (TIL-B), both switched memory cells and plasmablasts were expanded, as compared with nonmalignant epithelium. Moreover, pronounced skewing of Igλ/Igκ ratio was evident among TIL-Bs. By spectratype analysis on IgH, we confirmed a monoclonal expansion of the Vh7 family in TIL-B, also present in a tumor-associated LN. Sequencing the clonally expanded Vh7 revealed signs of somatic hypermutation. In conclusion, B lymphocytes in cancer patients exhibit signs of activation in tumor-associated tissues, likely induced by recognition of tumor Ags. Increased numbers of switched memory cells and plasmablasts in combination with clonal expansion and signs of somatic hypermutation suggest a CD4+ T lymphocyte–dependent antitumoral response, which may be exploited for immunotherapy.